2022
DOI: 10.3390/microorganisms10101876
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Functional Potential of Lactic Acid Bacteria Strains and Antimicrobial Effects in Minimally Processed Pomegranate (Punica granatum L. cv Jolly Red) Arils

Abstract: This study aimed to evaluate the antimicrobial activity of both cells, and cell-free supernatants (CFS) of 7 selected lactic acid bacteria (LAB) strains belonging to Limosilactobacillus fermentum (4 strains), Lacticaseibacillus paracasei (1 strain), Lacticaseibacillus rhamnosus (1 strain), and Enterococcus faecium (1 strain) species, against Listeria monocytogenes, Escherichia coli, Salmonella Typhimurium, Pseudomonas aeruginosa and Staphylococcus aureus, by both the agar-well diffusion and co-culture methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Co-culturing probiotics and pathogens is an effective method to evaluate the inhibitory ability of the former against the latter. Ben and his colleagues found that L. rhamnosus LBF 16 and L. paracasei LBF 19 exhibited the complete inhibition of E. coli when co-cultured [52]. Wang et al [53] reported that L. plantarum completely inhibited the growth of enterotoxigenic E. coli after 24 h of co-culturing.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culturing probiotics and pathogens is an effective method to evaluate the inhibitory ability of the former against the latter. Ben and his colleagues found that L. rhamnosus LBF 16 and L. paracasei LBF 19 exhibited the complete inhibition of E. coli when co-cultured [52]. Wang et al [53] reported that L. plantarum completely inhibited the growth of enterotoxigenic E. coli after 24 h of co-culturing.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Sakoui et al (2022) reported that strains of Enterococcus genus (Enterococcus faecium V6-112, Enterococcus faecalis JM102, Enterococcus mundtii MAV6B, Enterococcus gallinarum HBUAS52471, Enterococcus casseflavus APHG2) did not show gelatinase activity [21]. Ben Farhat et al (2022) also did not observe gelatinase activity in any of the LAB strains of Limosilactobacillus fermentum (4 strains), Lacticaseibacillus paracasei (1 strain), Lacticaseibacillus rhamnosus (1 strain) [162]. In another study, it was revealed that strains belonging to the Lactiplantibacillus plantarum and Enterococcus faecalis groups did not show gelatinase activities [158].…”
Section: Gelatinase Activitymentioning
confidence: 98%
“…This leads consumers to prefer foods that are not only healthy and easy to prepare [6][7][8][9][10] but also of high quality and safety, preferably without additives [7,9,11]. A wide range of ready-to-eat, refrigerated food products with longer shelf lives is available to meet these preferences [10][11][12][13][14]. Among these, a specific category of products known as minimally processed foods (MP) [7,15,16] has emerged.…”
Section: Introductionmentioning
confidence: 99%